A hidden curriculum for environmental topics in medical education: Impact on environmental knowledge and awareness of the students - Straßer, Patrick; Kühl, Michael; Kühl, Susanne J (GMS journal for medical education, 2023)
Climate change constitutes a major challenge. The higher education sector plays an important role in regard to climate change and the adaptation to its consequences. Various approaches toward the integration of environmental subject areas to higher education teaching have already been described in other studies, but there is a lack of data supporting the effectiveness of these approaches in changing not only the environmental knowledge of students, but also their awareness. To address this, the present study tracked whether student attitudes about the environment could be changed by implicitly addressing medically relevant environmental topics as part of an online seminar. Second semester students of molecular medicine attending a mandatory 14-hour online seminar, which was required to obtain additive key qualifications and which consisted of independent study phases as well as online class meetings, were divided into two groups: the intervention group (IG, n=27, thereof 20 in the pretest and 21 in the posttest) was exposed to medically relevant environmental topics, while the comparison group (CG, n=26, thereof 22 in the pretest and 21 in the posttest) was exposed to general, non-environmental medical topics. Surveys were conducted with standardized questionnaires before and after the seminar in order to study the influence on the students' environmental knowledge, awareness and other personal attitudes. While the seminar did not significantly change the environmental awareness in either group, the environmental knowledge of the IG was significantly increased by the group's exposure to environmental topics. In addition, the IG assessed its own environmental awareness regarding sustainable working methods in a laboratory as significantly higher after the seminar than the CG did, and some students of the IG had become more interested in issues relating to sustainability. The approach used to communicate environmental content mainly increased the environmental knowledge of students and piqued the interest of some students in climate-related and environmental topics. However, it was not possible to change deeper personal attitudes about environmental awareness, especially everyday behavior.